1968
DOI: 10.1111/j.1365-3180.1968.tb01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Zone Uptake of Soil‐applied Herbicides*

Abstract: Summary. Studies were conducted to determine the effects of herbicide placement at different zones of maize (Zea mays L.) and pea (Pisum sativwm L.) shoots below the soil surface after emergence. Soil was removed from around the shoots and replaced with herbicide‐treated soil. A wax barrier ensured separate exposure of the zones to treated soil. EPTC, chlorpropham, propham and sulfallate did not affect pea shoot growth, but in maize the shoot zone adjacent to the crown root node was extremely sensitive. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 7 publications
5
30
0
Order By: Relevance
“…the base of the coleoptile was the most sensitive zone to di-allate. Prendeville (1968) showed that the lower shoot, including the coleoptilar internode in wheat, oats and barley was the most sensitive region to 5-ethyl-jVl/Vdipropylthiolcarbamate (EPTC) while in sorghum, no such differential sensitivity existed. In maize the shoot region around the growing point and crown root node was the most sensitive region to isopropyl JV-phenylcarbamate (propham), isopropyl jV-(3-chlorophenyl)carbamate (chlorpropham) and EPTC (Prendeville, 1968).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…the base of the coleoptile was the most sensitive zone to di-allate. Prendeville (1968) showed that the lower shoot, including the coleoptilar internode in wheat, oats and barley was the most sensitive region to 5-ethyl-jVl/Vdipropylthiolcarbamate (EPTC) while in sorghum, no such differential sensitivity existed. In maize the shoot region around the growing point and crown root node was the most sensitive region to isopropyl JV-phenylcarbamate (propham), isopropyl jV-(3-chlorophenyl)carbamate (chlorpropham) and EPTC (Prendeville, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Prendeville (1968) showed that the lower shoot, including the coleoptilar internode in wheat, oats and barley was the most sensitive region to 5-ethyl-jVl/Vdipropylthiolcarbamate (EPTC) while in sorghum, no such differential sensitivity existed. In maize the shoot region around the growing point and crown root node was the most sensitive region to isopropyl JV-phenylcarbamate (propham), isopropyl jV-(3-chlorophenyl)carbamate (chlorpropham) and EPTC (Prendeville, 1968). The presence of adventitious roots on the shoots of maize and sorghum was shown to be significant in herbicide uptake and foliage injury with jV'-(3,4-dichlorophenyl) jVjV-dimethylurea (diuron), 4-ethylamino-6-isopropylamino-2-methylthio-l,3,5-triazine (ametryne) and 5-chloro-6-methyl-3-<-butyluracil (terbacil).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of reports (1)(2)(3)(4)(5)(6)(7) have been concerned with the site of uptake of EPTC in various plant species. In some species root exposure to the treated soil gave more injury than shoot exposure and in other species shoot exposure gave more injury (1,5).…”
Section: Introductionmentioning
confidence: 99%